Failure behavior and acoustic emission characteristics of shale after subjection to high temperature. Issue 6 (October 2021) - Huang, Linqi; Guo, Yide; Li, Xibing
Abstract: Uniaxial compression tests and acoustic emission (AE) monitoring on shale specimens with horizontal bedding planes and perpendicular bedding planes after subjection to high temperatures (25°C, 100°C, 150°C and 200°C) were performed to investigate the effect of high-temperature environment on shale in rock engineering. Results show that specimens in the two bedding directions experienced severe rockburst failure, and the increasing temperature made rockburst failure more intense. The rockburst phenomena for all the specimens were similar and consistent, including spalling, particle ejection and block collapse. Temperature had no significant effect on the failure mode of specimens with perpendicular bedding planes, while specimens with horizontal bedding planes turned to splitting with the increasing temperature. Fractal dimension of fragmentation increased with the increasing temperature, and that for specimens with perpendicular bedding planes increased much more than that for specimens with horizontal bedding planes. Before the peak, the cumulative AE counts can be divided into three stages by stress level of 40% and 80%.